Simulated JWST/NIRISS Transit Spectroscopy of Anticipated Tess Planets Compared to Select Discoveries from Space-based and Ground-based Surveys. (22nd February 2018) - Louie, Dana R.; Deming, Drake; Albert, Loic; Bouma, L. G.; Bean, Jacob; Lopez-Morales, Mercedes
Abstract: The Transiting Exoplanet Survey Satellite (TESS) will embark in 2018 on a 2 year wide-field survey mission, discovering over a thousand terrestrial, super-Earth and sub-Neptune-sized exoplanets ( R pl ≤ 4 R ⊕ ) potentially suitable for follow-up observations using the James Webb Space Telescope ( JWST ). This work aims to understand the suitability of anticipated TESS planet discoveries for atmospheric characterization by JWST 's Near InfraRed Imager and Slitless Spectrograph (NIRISS) by employing a simulation tool to estimate the signal-to-noise (S/N) achievable in transmission spectroscopy. We applied this tool to Monte Carlo predictions of the TESS expected planet yield and then compared the S/N for anticipated TESS discoveries to our estimates of S/N for 18 known exoplanets. We analyzed the sensitivity of our results to planetary composition, cloud cover, and presence of an observational noise floor. We find that several hundred anticipated TESS discoveries with radii 1.5 R ⊕ < R pl ≤ 2.5 R ⊕ will produce S/N higher than currently known exoplanets in this radius regime, such as K2-3b or K2-3c. In the terrestrial planet regime, we find that only a few anticipated TESS discoveries will result in higher S/N than currently known exoplanets, such as the TRAPPIST-1 planets, GJ1132b, and LHS1140b. However, we emphasize that this outcome is based upon Kepler -derived occurrence rates, and that co-planar compact multi-planet systems (e.g., TRAPPIST-1) may be under-represented in the predicted TESS planet yield. Finally, we apply our calculations to estimate the required magnitude of a JWST follow-up program devoted to mapping the transition region between hydrogen-dominated and high molecular weight atmospheres. We find that a modest observing program of between 60 and 100 hr of charged JWST time can define the nature of that transition (e.g., step function versus a power law).